Hubungan Status Pekerjaan Dengan Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Pariaman - Miftakhul Zanah (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Introduction : Breastfeeding in Indonesia maintains not yet been fully implemented cum the provision of exclusive breastfeeding is still very low, especially for working mothers. From the results of observations carried out by researchers in the Pariaman Community Health Center working area, data was facile that 7 out of 41 working mothers who breastfed did not give exclusive breast milk to their babies, and 14 out of 24 non-working mothers who breastfed give exclusive breast milk to their babies. Objective: This research is to determine the relationship between employment status and exclusive breastfeeding. Method: This type of research is quantitative research by the type of research being analytical, with a cross-sectional design. The method used is probability sampling with a simple random sampling technique. The samples taken were 65 mothers who had babies aged 6-12 months in the working area of ​​the Pariaman Community Health Center. Data collection uses a questionnaire containing the characteristics of the respondents. After tabulation, the existing data is analyzed using univariate and bivariate analysis. Results: This research was carried out by analyzing the relationship between employment status and exclusive breastfeeding. The calculation results obtained using the Chi-Square statistical test obtainable a p-value = 0.001 < (α 0.05), meaning there is a meaningful connection between employment status and breastfeeding. Exclusively in the working area of ​​Pariaman Community Health Center in 2023. Conclusion: There is a significant relationship between employment status and exclusive breastfeeding. Suggestion: Mothers who breastfeed are recommended to provide exclusive breast milk for six months by expressing breast milk before going to work